Analysis of Mangrove Vegetation Community Structure in Bukit Batu Village, Bukit Batu District, Bengkalis Regency, Riau - Putri, Rahadiva Anjani; Samiaji, Joko; Nasution, Syafruddin (Journal of Coastal and Ocean Sciences, 2026)
The mangrove ecosystem in Indonesia is rich in biodiversity and plays an important role in maintaining coastal balance, but it is currently under pressure from human activities. This study was conducted in December in Bukit Batu Village, Bukit Batu District, Bengkalis Regency, an area with an extensive mangrove ecosystem that is vulnerable to anthropogenic pressure. The study aims to identify mangrove species and analyze density, importance value index (INP), and vegetation zonation patterns using a field survey at three stations. Stations were determined using purposive sampling, and mangrove observations were conducted using the line transect method, with each station consisting of 3 transects and each transect consisting of 3 plots (10m×10m for trees, 5m×5m for saplings, and 2×2 m2 for seedlings). The results showed six mangrove species, i.e., Rhizophora apiculata, Avicennia alba, Sonneratia alba, Bruguiera gymnorrhiza, Xylocarpus granatum, and Nypa fruticans. Environmental conditions were dominated by mud substrate, with>75% containing 12.31–22.34% organic matter. Tree density ranged from 833.33–1,533.33 ind/ha and was dominated by R. apiculata, which also had the highest INP. Statistical analysis indicated no significant differences in density among stations (p>0.05). The zonation pattern showed differences in species composition between the sea and the land, at Station I, zones I–R. Apiculata, B. gymnorrhiza, and N. fruticans dominated III. At Station II, zone I was dominated by S. alba, while zones II–III were dominated by R. apiculata. At Station III, zones I–II were dominated by R. apiculata with X. granatum in zone II, and zone III was dominated by X. granatum.